Entre imagens cinema e imagens escola, movimentando o pensamento com a formação de professores - Rodrigues, Larissa Ferreira (2015)
This research deals with the study of movements of thought at the network training with elementary school teachers. It seeks to problematize the construction of non-dogmatic everyday educational processes in school, through the articulation of movies and school images, displayed, shared and created within the conversations network in a municipal school in Vitória / ES along 2013 and 2014. It presents a problematic field dedicated to understand which movements of thought are produced from the use of movie images at the conversations network with teachers attending the continuing education training, which is based on a research cartography that articulates the virtual mapping present at CAPES thesis database and the cinecartography present at the everyday school life, in the two folds of time. It weaves a theoretical debate which is composed by lines of thought, especially the ones of Bergson (2006a; 2006b), Carvalho (2008; 2009; 2010; 2012) Deleuze (1988; 1991; 1992; 1995; 1996; 2003; 2006; 2007; 2010; 2011), Foucault (1979; 1999 2006a; 2006b; 2008), Guéron (2010; 2011), Pelbart (2011), Sauvagnargues (2009), among others. The theoretical-methodological options establish a research field at the intersection between the school routine studies and the cartographic research, taking the plane immanence as the material world for the occurrence of events. For data production, it uses the participant observation, the records in field diary, considered as a clear description, as well as those clear narratives that emerged from the conversations network with the school-characters (teachers), which configure themselves as moving image narrative research. The discussion of the produced data is organized in seven chapters. The considerations are presented into three main movements of thought grouping, provoked by the film images within the teachers’ conversations network: “cinescola-clichés”, “imagensformação docente” and “cristaisescolas”. It highlights that there is not a reality which holds the truth about teachers training, but there are cuts, perceptions, conditions and productions of truths that interlace the different ways of existing and (re)existing in the Brazilian education. The “telasescolas”, as well as the big screen, present and surround us with a world that articulate a “cinescola cliché”, “imagensformação docente” and “cristaisescolas”, which go beyond the straight and dogmatic thinking, as they display movie images and school images, other movements of thought due to the teacher training, enhancing the educational researches not to go in a pursue of 'search of a lost time, but a time to be rediscovered’, making us further believe in this world and in education.